Relating soil C and organic matter fractions to soil structural stability - Jensen, Johannes L.; Schjønning, Per; Watts, Christopher W.; Christensen, Bent T.; Peltre, Clément; Munkholm, Lars J. (Geoderma, 2019)
Soil organic matter (SOM) is important for maintaining soil structural stability (SSS). This study quantified the influence of soil organic carbon (SOC) and different organic matter components on various SSS measures. We used a silt loam soil with a wide range of SOC (8.0–42.7 g kg−1 minerals) sampled in spring 2015 from the Highfield Ley-Arable Long-Term Experiment at Rothamsted Research. Four treatments were sampled: Bare fallow, continuous arable rotation, ley-arable rotation, and grass. Soils were tested for clay dispersibility (DispClay), clay-SOM disintegration (DI, the ratio between clay content without and with SOM removal) and dispersion of particles <20 μm. The SSS tests were related to SOC, permanganate oxidizable carbon (POXC), hot water-extractable carbon (HWC), mid-infrared photoacoustic spectroscopy (FTIR-PAS) and mineral fines/SOC ratio. SSS increased with increasing content of SOM components. The relationships between SOM components and SSS followed a broken-stick regression with a change point at ~23.0 g SOC kg−1 minerals (clay/SOC~10) coinciding with a change from the tilled treatments to the grass treatment. We found a greater influence of SOC, POXC and HWC on SSS at contents below the change point than above. A stronger linear relation between POXC and DispClay compared to SOC and HWC suggests that POXC was a better predictor of the variation in DispClay. POXC and HWC were less related to DI than SOC. The grass treatment had a very stable structure, shown in all SSS tests, probably due to the absence of tillage and large annual inputs of stabilizing agents. This suggests that a change in management from arable rotation to permanent grass is one effective tool for improving SSS. •Soil structural stability increased with an increase in SOM components.•The effect of increasing SOM components was greater at low contents.•The change point for soil structural stability was at a clay/SOC ratio close to 10.•Grassland soil has a very stable structure compared to tilled soil.